Exploring The Lane Changing Duration Time On U-turn Facility - MOHD NOOR, NUR AQILAH; Ahmad Termida, Nursitihazlin (Recent Trends in Civil Engineering and Built Environment, 2022)
Driver’s behaviour while making a Lane Changing (LC) in the shortest time could lead to an accident. At a U-turn facility, drivers need to make decisions to perform a U-turn and merge to the major road or the target lane and apply Mandatory LC type. Thus, objective of this study aims to examine the LC behaviour among drivers at U-turn facility by measuring the LC duration time (in seconds) of the vehicles from U-turn facility to the target lane (major road). The LC duration time was collected through a manual observation by using a mobile application and video camera. The observation was conducted in two weekdays for three peak hours (morning, afternoon and evening). The descriptive statistics was used to analyzed the data for day 1 and day 2 by using a Microsoft Excel software in order to achieved the study objectives. The findings show that the LC duration time for the different types of vehicle. In conclusion, the LC duration time on day 2 yields the same result as day 1, namely that motorcycles have the shortest mean of LC duration since they are small and light when making a LC maneuver. In contrast to other vehicle categories, heavy trucks had the highest mean LC duration because they carried heavy loads and needed more time to make a LC maneuver compared to other vehicle types. Therefore, LC are able to identified the characteristics of drivers’ behaviour while making lane changing at U-turn facility to the target lane.